1994
DOI: 10.1038/bjc.1994.106
|View full text |Cite
|
Sign up to set email alerts
|

Soluble E-cadherin fragments increased in circulation of cancer patients

Abstract: Summary Monoclonal antibodies were raised against human placental soluble E-cadherins and used in an immunoenzymometric assay to detect soluble E-cadherins in biological fluids. The E-cadherin assay was accurate enough to quantitate the concentration of soluble E-cadherin in the cell culture supernatants. Immunoreactive E-cadherins, identified as existing in the soluble form in normal serum, were shown to have apparent lower molecular mass (approximately 80 kDa) than intact molecules of E-cadherin. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
131
1
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 29 publications
6
131
1
4
Order By: Relevance
“…The soluble cleaved form of E-cadherin has been observed in serum under non-pathological conditions, but increased levels of the soluble form have been detected in patient peripheral blood samples 24,54 and urine samples 55 in a variety of diseases. 21 It has been suggested that the 80-kDa soluble fragment may serve as a useful biomarker of disease progression for a number of cancers, including prostate, 23 gastric, 24 hepatocellular 24 and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The soluble cleaved form of E-cadherin has been observed in serum under non-pathological conditions, but increased levels of the soluble form have been detected in patient peripheral blood samples 24,54 and urine samples 55 in a variety of diseases. 21 It has been suggested that the 80-kDa soluble fragment may serve as a useful biomarker of disease progression for a number of cancers, including prostate, 23 gastric, 24 hepatocellular 24 and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…21 It has been suggested that the 80-kDa soluble fragment may serve as a useful biomarker of disease progression for a number of cancers, including prostate, 23 gastric, 24 hepatocellular 24 and bladder cancer. 55 There has also been a correlation between tumor stage, histological grade and elevated levels of soluble E-cadherin, likely because the detection of soluble E-cadherin has been associated with increased invasiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the association between the cell-cell adhesion molecule, E-cadherin, and cytoskeletal protein, β-catenin has been shown to be vulnerable to enzymatic attack by multiple MMPs, including MMP-9 and MMP-2 [42,44,45]. Proteolytic cleavage of the N-terminal extracellular domain of E-cadherin by MMPs results in the shedding of E-cadherin and formation of extracellular domain fragments ranging in size from 50 to 85 kDa, that are often secreted into the conditioned media of cultured cells [46] and have been detected in vivo in urine, blister fluid of cutaneous diseases and the circulation of cancer patients [47][48][49]. Interestingly, MMP inhibitors have been shown to stabilize cadherin junctions and more specifically, the MMPI, GM6001, can suppress Ecadherin shedding [23,42,43].…”
Section: Mmp and Ascmentioning
confidence: 99%
“…Proteolytic cleavage of E-cadherin from the cell surface may account for the soluble form (Matsuura et al, 1992), which has been found in serum (Katayama et al, 1994a;Griffiths et al, 1996) and in urine (Katayama et al, 1994b;Banks et al, 1995) with elevated levels in patients with a variety of cancers. Following the recent finding of elevated serum sE-cadherin concentrations in patients with bladder tumours (Griffiths et al, 1996), we have performed a preliminary cross-sectional study measuring urinary sE-cadherin levels in patients with bladder cancer, non-neoplastic conditions and healthy volunteers and compared these with urinary total protein levels to establish whether such measurements may be of use clinically for diagnostic or monitoring purposes.…”
mentioning
confidence: 99%